Wavelet-based transmissibility for the analysis of time-variant systems. (November 2020) - Dziedziech, Kajetan; Staszewski, Wiesław J.
Highlights: Engineering system often exhibits time-variant behaviour. Wavelet-based transmissibility and coherence are proposed for the analysis of such systems. The proposed method utilises wavelet auto- and cross-spectra. The method is illustrated using simulated and experimental examples of time-variant systems. The results demonstrate the great potential for the analysis of time-variant systems. Abstract: The wavelet-based transmissibility – that extends the concept of direct transmissibility - is proposed for the analysis of the time-variant system. The method is based on auto- and cross-wavelet spectra. The proposed approach is demonstrated using a simulated lumped parameter system and experimental data from a time-variant frame-like structure. The wavelet-based transmissibility and associated with it the wavelet-based coherence are presented and compared with the classical analysis based on frozen spectra and the input-output analysis that involves input-output characteristics, i.e. the wavelet-based Frequency Response Function and coherence. The results show that the proposed output-only approach can be used to reveal the time-variant behaviour of analysed systems.